Răspunsuri

Cel mai inteligent răspuns!
2014-06-28T21:53:35+03:00
X( 1/1*2  + 1/2*3  +  1/3*4 +...+1/2009*2010 + 1/2010*2011) =2010

1/1*2=  1/1 -1/2
1/2*3=  1/2 -1/3
1/3*4=   1/3 -1/4
......................................................
1/2009 *2010= 1/2009 -1/2010
1/2010*2011= 1/2010- 1/2011

S= 1/1- 1/2011   aducem la acelasi numitor

S= (2011-1)/2011
S=2010/2011

x*  2010/2011= 2010

2010x/2011=2010

x=2011*2010/2010

x=2011
Comentariul a fost şters
multumesc mult, la fel ;)
Comentariul a fost şters